2023
DOI: 10.1007/s11325-023-02776-6
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of central sleep apnea to severe sleep apnea hypopnea syndrome

Abstract: Purpose Central sleep apnea (CSA) is usually distinguished from obstructive sleep apnea (OSA). In fact, CSA is often a component of severe sleep apnea hypopnea syndrome (SAHS), rather than occurring alone. We investigated the clinical characteristics and polysomnography (PSG) parameters of CSA components in patients with severe SAHS. Methods The clinical characteristics and PSG parameters were retrospectively analyzed. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…This results in modifications of sleep structure. Furthermore, OSA may also affect the central nervous system of the child, which ultimately leads to abnormal psychological and behavioural development (Urbano et al, 2021;Zhang et al, 2019). In this study, we found that OSA is more likely to occur in male children, which is consistent with the findings of Kuehni et al (2008).…”
Section: Discussionsupporting
confidence: 88%
“…This results in modifications of sleep structure. Furthermore, OSA may also affect the central nervous system of the child, which ultimately leads to abnormal psychological and behavioural development (Urbano et al, 2021;Zhang et al, 2019). In this study, we found that OSA is more likely to occur in male children, which is consistent with the findings of Kuehni et al (2008).…”
Section: Discussionsupporting
confidence: 88%